DETERMINING PRACTISING OF BREAST SELF-EXAMINATION AND BREAST CANCER RISK FACTORS IN WOMEN AGED TWENTY YEARS AND OVER LIVING IN A RURAL AREA OF CORUM - Gülay Yılmazel (European Journal of Breast Health, 2013)

(untitled)
Objective:This study was performed to determine breast self examination practices and breast cancer risk factors in women aged twenty years and over living in a Corum rural area.Materials and Methods:This descriptive study was conducted in two villages (Figani and Eskice) which were located in the province of Corum Mecitozu. The population of the study consisted from 230 women who were aged twenty years and over registered to Figani and Eskice Village Health House. The study, which included 172 women aged twenty years and over were visited in their homes by the researcher and students attending a public health nursing lesson course. The data of the study were collected by face to face interviews with a 28 item questionnaire which investigated the socio-demographic characteristics of women, reproductive characteristics, investigating risk factors for breast cancer. In the assesment of data, number,, percentage, arithmetic mean and Pearson Chi-square tests were used. p<0.01 and p<0.05 were considered statistically significant.Results:Variables such as older ages, lower education levels, family history of breast cancer, menopause, used OKS in the past defined as risk factors for breast cancer which were affecting BSE in women living in rural areas (p<0.01, p<0.05).Conclusion:Health care professionals responsible for the delivery of health services in rural areas for prevention of breast cancer should provide community based education on-site with mobile services about healthy lifestyle behaviors and early diagnosis and in this training should take into account health communication strategies.